DIGITAL AUDIT TECHNOLOGIES IN ACCOUNTING INFORMATION SYSTEMS: A SYSTEMATIC LITERATURE REVIEW OF CONTEMPORARY TRENDS AND PROFESSIONAL IMPLICATIONS - Herdiana, Krisna; Nugrahanti, Trinandari Prasetya (jfpublisher, 2025)
Contemporary business environments have experienced unprecedented technological advancement, fundamentally transforming traditional auditing practices within accounting and information systems. Digital transformation introduces sophisticated technologies that challenge conventional audit methodologies, necessitating comprehensive examination of emerging trends and implications. Despite expanding literature on technological integration in auditing, substantial gaps remain in understanding digital audit adoption landscapes, particularly regarding dominant technologies, implementation barriers, and organizational impacts. This investigation explores prevailing trends, identifies predominant technologies, assesses associated benefits and challenges, and examines digital auditing implications within accounting and information systems domains. The research employs systematic literature review methodology, analyzing ten peer-reviewed scholarly articles published between 2020-2025, sourced from Scopus and SINTA databases. Findings reveal that big data analytics, artificial intelligence, blockchain technology, robotic process automation, and cloud computing constitute primary technological foundations of modern digital auditing. These innovations demonstrate substantial contributions toward enhanced audit quality, transformed auditor roles, and strengthened organizational governance structures. However, implementation encounters significant obstacles including adoption disparities among firms, insufficient digital competency among practitioners, and heightened data security concerns. The study recommends developing adaptive strategies for human resource development, comprehensive technology integration frameworks, and sustainable digital audit policy formulation.